Rainfall-Induced Shallow Slope Failure and Mechanism-Based Stabilization of Telecommunication Infrastructure - Khoeri, Heri; Nugroho, Panji; Rizqullah, Naufal Rafif (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2026)
Rainfall-induced shallow slope failure is a recurrent geotechnical hazard in tropical regions, particularly for slopes supporting critical infrastructure. This paper presents a case study of a shallow translational failure at a telecommunication facility in Batam, Indonesia, following prolonged heavy rainfall. The study integrates subsurface investigation (six boreholes with SPT, electrical resistivity surveys, and laboratory testing) to establish engineering stratigraphy consisting of three units: an upper loose to medium silty sand (Unit I), a medium to dense sand (Unit II), and competent sandstone (Unit III). Limit-equilibrium stability analyses were performed under dry and various rainfall infiltration scenarios, with rainfall effects represented by a rising perched water table (PWT). Results show that the slope is highly stable under dry conditions (factor of safety, FS ? 1.996). However, as the PWT rises from 4 m to 1 m below ground surface, the FS progressively decreases from 1.384 to 0.931, indicating that rainfall-induced pore water pressure increase and loss of matric suction are the governing failure mechanisms. Based on this mechanism, a combined mitigation strategy incorporating surface drainage improvement and soldier pile reinforcement was developed. Under the most critical rainfall scenario (PWT at 1 m depth), the reinforced slope achieves an FS of approximately 1.593, exceeding the recommended minimum of 1.5 for strategic infrastructure. The study highlights the necessity of explicitly incorporating rainfall-driven groundwater rise into slope stability assessments for critical facilities in tropical environments and provides a mechanism-based framework for effective stabilization.